Analisis Integrasi TIK Berbasis Platform Digital pada Pembelajaran untuk Meningkatkan Kesadaran Kewarganegaraan sebagai Upaya Mendukung SDGs - Arif Sobirin Wibowo; Wigena , Ida Bagus Weda; Musabikha M, Rosikh (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2025)
One of the programs in the Merdeka curriculum focuses on strengthening the outcomes of the Pancasila Student Profile, developed in accordance with themes set by the government. This character development effort can be achieved through the application of the "Pancasila Student Profile," which aligns with the characteristics of the Merdeka learning curriculum. Given the rapid advancement of information and communication technology (ICT), integrating ICT into education becomes essential to ensure that Pancasila education remains effective and competitive in an ever-changing global era.The research method used in this study is a qualitative approach with a case study design. The research site is Madrasah Aliyah Asy-Syakur Bojonegoro, and the subjects are teachers and students. Data collection occurs in several stages, including in-depth interviews, classroom observations, and document analysis. The validity of the research findings is strengthened through data triangulation. Based on the research results, teachers perceive the main benefit of using digital platforms as an increase in student interest in Pancasila education. Meanwhile, students become more enthusiastic about understanding their rights and obligations as citizens and participating in social activities. The use of digital media in teaching has also been beneficial for students. Students involved in social projects related to community importance through digital platforms are more motivated and engaged in learning. This is because digital technology helps students understand the significance of their education and daily lives.